Oligodendrogliomas: Molecular Biology and Treatment - Bromberg, Jacolien E. C.; van den Bent, Martin J. (The oncologist (Dayton, Ohio), 2009)
Learning Objectives Evaluate the current challenges in the histological diagnosis of oligodendroglial tumors and apply best practices to optimize patient outcomes. Analyze the molecular alterations in different subsets of tumors with oligodendroglial morphology. Formulate treatment options for your patients with newly diagnosed and recurrent oligodendroglial tumors. This article is available for continuing medical education credit at CME.TheOncologist.com. Oligodendroglial tumors continue to receive much attention because of their relative sensitivity to chemotherapy. The histological diagnosis of oligodendroglial tumors is subject to considerable interobserver variation. The revised 2007 World Health Organization classification of brain tumors no longer accepts the diagnosis “mixed anaplastic oligoastrocytoma” if necrosis is present; these tumors should be considered glioblastomas (perhaps with oligodendroglial features). The 1p/19q codeletion that is associated with sensitivity to chemotherapy is mediated by an unbalanced translocation of 19p to 1q. Randomized studies have shown that patients with 1p/19q codeleted tumors also have a better outcome with radiotherapy. Histologically more atypical tumors are less likely to have this 1p/19q codeletion; here, other alterations usually associated with astrocytic tumors are often found. Some patients with tumors with classic histological features but no 1p/19q codeletion still have a very favorable prognosis. Currently, the best approach for newly diagnosed anaplastic oligodendroglial tumors is unclear. Early adjuvant chemotherapy does not provide a better outcome than chemotherapy at the time of progression. The value of combined chemoirradiation with temozolomide has not been proven in these tumors, and could at least theoretically be associated with greater neurotoxicity. Tumors with 1p and 19q loss can also be managed with early chemotherapy, while deferring radiotherapy to the time of further progression. The presently available second‐line chemotherapy results are modest, and better salvage treatments are necessary. The molecular explanation for the greater sensitivity of 1p/19q codeleted tumors is still unclear, and this could, in part, be explained by more frequent MGMT promoter gene methylation. This manuscript reviews recent developments in the research and treatment of oligodendroglial tumors.